2012
DOI: 10.1088/0957-4484/23/8/085102
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and tissue distribution of neutron-activated zinc oxide nanoparticles and zinc nitrate in mice: effects of size and particulate nature

Abstract: Although zinc oxide nanoparticles (ZnONPs) have been applied in nanotechnology, their kinetics and tissue distribution in vivo are unknown. Here we compared the kinetics and tissue distribution of 10 nm (65)ZnONPs, 71 nm (65)ZnONPs and (65)Zn(NO(3))(2) in mice after intravenous injection. The areas under the curves and the half-lives in the second compartment of (65)Zn(NO(3))(2) were greater than those of (65)ZnONPs; the kinetic parameters were similar for both (65)ZnONPs. However, the tissue distributions for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 25 publications
0
36
0
Order By: Relevance
“…32 In this regard, ZnO NPs would encounter diverse immune cells in the human body, thus damaging immune tissues and organs. However, the immunotoxicity of ZnO NPs in relation to the size and charge of ZnO NPs is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…32 In this regard, ZnO NPs would encounter diverse immune cells in the human body, thus damaging immune tissues and organs. However, the immunotoxicity of ZnO NPs in relation to the size and charge of ZnO NPs is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…15 Various studies have shown that ZnO NPs with various shapes, such as rods and spheres, probably cause neurotoxicity due to their ability to access the brain. [16][17][18] Moreover, the olfactory brain route has also been reported as a potential route for ZnO NPs transfer into the brain. 19 However, information regarding the neurotoxic effects of ZnO NPs is scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The kinetics of neutron-activated 65 ZnO nanoparticles of two different sizes (10 and 71 nm) was evaluated in mice after intravenous injection, with 65 ZnNO 3 as a control; 30 the kinetic parameters for the two nanoparticle sizes were similar, but greater plasma AUC and t ½ values were found for 65 ZnNO 3 than 65 ZnO nanoparticles. These results are in good agreement with the report by Paek et al, described earlier.…”
mentioning
confidence: 99%